Site-directed mutagenesis of the C-terminal of the Newcastle disease virus V protein - Tham, May Ling; Yusoff, Khatijah; Othman, Siti Sarah; Chia, Suet Lin (AEPress, 2022)
Newcastle disease virus (NDV) is a paramyxovirus that is highly pathogenic to poultry causing severe economic loss worldwide. The non-structural V protein is one of the virulence factors of the virus. It antagonises the interferon of the host innate immunity in order to allow successful virus replication in the host cells. However, detailed investigation of recombinant NDV expressing mutated V protein is scarce. In this study, a mesogenic recombinant NDV expressing GFP (rAF-GFP) was used to investigate the relation of V protein mutation on virus pathogenicity. Site-directed mutagenesis was performed using overlapping PCR to introduce four premature stop codons 456G>T, 537G>T, 624C>T and 642G>T in the V gene reading frame. The virus was then rescued and propagated in embryonated chicken eggs. However, instead of the substituted thymine, this nucleotide was mutated into cytosine in three rescued mutants, while 537G>T mutant could not be rescued. As a result, the premature stop codon was substituted with other amino acid and the V protein was expressed in full length. The pathogenicity type of the rAF (456G>T>C), rAF (624C>T>C), and rAF (642G>T>C) mutants remained to be as in mesogenic strains, suggesting that substituted amino acids were functionally interchangeable with the original amino acids present in V protein. It appears that an intact V protein is important for the virus survival. This study explored the possibility of V protein mutation in NDV through exploiting genetic engineering and warrants a further investigation on modifying mutations on a conserved protein in NDV or other paramyxoviruses. Keywords: Paramyxoviridae; Newcastle disease virus; V protein; C terminal; virulence factor.